Ireland : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Ireland. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that the Irish economy continues to grow at a rapid pace, well above the European Union average. Although headline data are distorted by the volatility of multinationals' activity, the broad recovery of (modified) domestic demand (4 percent in 2017) underpins the expansion. Strong labor market performance brought the unemployment rate down to below 6 percent by April 2018. Although wage pressures emerged in some sectors, inflation remained subdued, mainly reflecting the pass-through of pound sterling depreciation. Public finances continued to improve on the back of strong output growth, while the public debt burden declined slightly to 68 percent of GDP. The outlook remains broadly positive but with externally-driven downside risks.